Influence of parotid lymph node metastasis on distant metastasis in parotid gland cancer - Meng, Fan; Yuan, Junhui; Zhang, Xu; Liu, Jun; Li, Hailiang (Frontiers in Oncology, 2023)
Background: To analyze the impact of the number and extranodal extension (ENE) of positive parotid lymph nodes (LNs) on distant metastasis in parotid cancer. Methods: Patients with surgically treated parotid cancer were retrospectively enrolled. The hazard ratios (HRs) of the number and ENE of positive parotid LNs on distant metastasis free survival (DMFS) were evaluated. Results: In Cox model, the groups with none and one positive LN had comparable 10-year DMFS, but those with two positive LNs had a HR of 2.11 (95% CI: 1.36-5.29), and those with three or more positive LNs had a HR of 3.31 (95% CI: 2.05-8.43). The presence of ENE in parotid LNs did not impact the DMFS (p=0.462; HR: 2.17; 95% CI: 0.84-6.17). Conclusion: Parotid LN metastasis was associated with decreased DMFS, this effect was mainly driven by the number of positive LNs rather than ENE.